Life cycle assessment of stabilization and solidification of heavy-metal contaminated sandy soil using sodium carbonate-activated volcanic ash-based geopolymer - Alireza Komaei; Arman Moazami; Hamidreza Mirzaei; Abbas Soroush (Case Studies in Construction Materials)
This study investigates the remediation of soils contaminated with hazardous heavy metals—lead (Pb2 +), chromium (Cr3+), and cadmium (Cd2+)—using a Portland cement and Na2CO3-activated volcanic ash-based geopolymer for stabilization and solidification. Compared to conventional activators like NaOH and Na2SiO3, Na2CO3 offers superior environmental sustainability, cost-effectiveness, and a reduced carbon footprint. Experimental results demonstrate significant improvements in unconfined compressive strength (UCS), surpassing the EPA threshold, and toxicity characteristic leaching procedure (TCLP) tests reveal a substantial reduction in metal leachability. A key finding is the role of a small dosage of Portland cement in accelerating geopolymerization, enhancing early-stage strength development, and improving heavy metal immobilization. The hybrid system capitalizes on the synergistic effects of sodium aluminosilicate hydrate (NASH) and calcium silicate hydrate (CSH) gels, which physically encapsulate heavy metals within a dense matrix. Additionally, chemical precipitation under alkaline conditions facilitates the formation of stable hydroxides and carbonates, further restricting metal mobility. Ion exchange and lattice substitution contribute to immobilization, particularly for Pb2+ and Cd2+, while Cr3+ integrates into aluminosilicate structures. The final stabilization stage involves crystalline phase formation, enhancing the long-term stability of immobilized metals. Furthermore, a life cycle assessment (LCA) underscores the environmental advantages of Na2CO3 activation over conventional cement-based stabilization.